2003
DOI: 10.1161/01.hyp.0000084634.97353.1a
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of 20-HETE Formation Promote Salt-Sensitive Hypertension in Rats

Abstract: Abstract-This study examined whether chronic blockade of epoxyeicosatrienoic acids (EETs) and/or 20-hydroxyeicosatetraenoic acid (20-HETE) formation promotes development of salt-sensitive hypertension. Changes in blood pressure, renal cytochrome P450 metabolism of arachidonic acid, and 20-HETE excretion in response to a high salt diet were measured in rats chronically treated with 1-aminobenzotriazole (ABT, 50 mg/kg per day) to block EETs and 20-HETE formation or N-hydroxy-NЈ-(4-butyl-2 methylphenyl) formamidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 42 publications
4
65
0
Order By: Relevance
“…Previous studies have demonstrated that the induction of the renal CYP4A enzyme attenuates the development of hypertension in Dahl salt-sensitive rats 15,16,21 and that the inhibition of 20-HETE, a metabolite of CYP4A, causes hypertension. 19,27 Additionally, the antihypertensive actions of 20-HETE can be attributed to inhibition of sodium transport by the proximal tubule and thick ascending limb of the loop of Henle. 14,20,22 Blockade of ion transport in freshly isolated proximal tubules by ET-1 is attenuated by inhibiting 20-HETE synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the induction of the renal CYP4A enzyme attenuates the development of hypertension in Dahl salt-sensitive rats 15,16,21 and that the inhibition of 20-HETE, a metabolite of CYP4A, causes hypertension. 19,27 Additionally, the antihypertensive actions of 20-HETE can be attributed to inhibition of sodium transport by the proximal tubule and thick ascending limb of the loop of Henle. 14,20,22 Blockade of ion transport in freshly isolated proximal tubules by ET-1 is attenuated by inhibiting 20-HETE synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 20-HETE has actions to reduce sodium transport and, like ET B receptor activation, has been implicated in saltdependent hypertension. [17][18][19][20][21] Previous studies have provided evidence that 20-HETE contributes to ET-1-mediated natriuretic responses. 22 Blockade of CYP4A and 20-HETE prevented the increase in urinary sodium excretion produced by ET-1.…”
mentioning
confidence: 99%
“…The kidneys were rapidly removed and the renal cortex and outer medulla were collected and homogenized separately in 3 ml of a 10 mM potassium buffer (pH 7.7) containing 250 mM sucrose, 1 mM EDTA, and 0.1 mM phenylmethylsulfonyl fluoride (PMSF). Microsomes were prepared as previously described (14). Briefly, homogenates were centrifuged at 3,000 g for 5 min to remove large tissue fragments, and the supernatants were centrifuged at 9,000 g for 15 min to remove mitochondria and nuclei.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the fawn-hooded rat has a genetic defect in renal autoregulation that results in early onset glomerular hypertension, followed by the accelerated development of renal disease (88). Numerous factors are known to govern renal autoregulation (84), including 20-hydroxyeicosatetraenoic acid (20-HETE) (89,90), and hence genetic alterations in any of these mediators could also lead to an abnormal autoregulatory response and increase the risk for progression in the subject with essential hypertension.…”
Section: Why Does Hypertension Progress In Some Subjects But In Othermentioning
confidence: 99%